Self-assembly of virus capsids decorated with block copolymers: a simulation study. Issue 1 (5th December 2016) - Dutt, Meenakshi; Chong, Leebyn; Libring, Sarah; Karra, Vyshnavi
Abstract: Abstract : Self-assembly of biocompatible nanoparticles is part of a promising field in drug delivery and biomaterials. Virus capsids are an example of nanoparticles capable of being tethered with functional groups for specific targeting. There have been experimental efforts on grafting polymers to virus capsids to synthesize tailored nanostructures. To provide insight at the nanoscale, we perform a highly coarse-grained molecular dynamics study, simulating the self-aggregation of cowpea mosaic virus (CPMV) capsids decorated with polyethylene glycol (PEG) and PEG polylactic acid (PLA) block polymers. We examined the effects of grafting architecture and volume fraction on equilibrated clusters. Characterization of the aggregation dynamics are summarized by the radius of gyration of the clusters, coordination number distributions, and average cluster size. When the system and methods are parameterized with respect to atomistic models or empirical results, the results can serve as the basis in broadly mapping the theoretical design space for controlled self-assembly of polymer-decorated virus capsids.